(3aVGFd HjJ GdebOS hGdNdjd hGdTGes - (3CHh GdeYGdj eTQa Hf eQLj Hf EHQGgje GdebOSj, GHf eQLjs
(3ChdgG (B:s
(3Ke Ef SGFdkG SCdfi Gf CPcQ LejY eG GfJgi Edi ef aVGFd GdeSLO GdebOS s
(3fSNI eUhQI Yf fSNI LGeYI JhHfLfs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B227s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B567 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B198 s
Keywords: (3GdJGQjNs